GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 449 species occurrences available in GBIF matching the query: TaxonKey: Dromaius novaehollandiae (Latham, 1790) HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Specimen. The dataset includes 449 records from 22 constituent datasets: 1 records from OEH Atlas of NSW Wildlife. 32 records from Australian National Wildlife Collection provider for OZCAM. 1 records from QLD DERM Coastal Bird Atlas (Trial). 10 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 123 records from Museum Victoria provider for OZCAM. 5 records from CRCM Vertebrate Collection. 2 records from SA Fauna (BDBSA). 2 records from SBMNH Vertebrate Zoology. 3 records from Northern Territory Museum and Art Gallery provider for OZCAM. 40 records from Western Australian Museum provider for OZCAM. 6 records from UWBM Ornithology Collection. 1 records from Naturalis Biodiversity Center (NL) - Aves. 2 records from WFVZ Bird Collections. 3 records from AMNH Bird Collection. 1 records from MVZ Egg and Nest Collection (Arctos). 43 records from Queensland Museum provider for OZCAM. 14 records from UMMZ Birds Collection. 3 records from MSB Bird Collection (Arctos). 4 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 83 records from Australian Museum provider for OZCAM. 4 records from MVZ Bird Collection (Arctos). 66 records from South Australian Museum Australia provider for OZCAM. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences